S-Ketamine Pretreatment Alleviates Anxiety-Like Behaviors and Mechanical Allodynia and Blocks the Pro-inflammatory Response in Striatum and Periaqueductal Gray From a Post-traumatic Stress Disorder Model - Yang, Shuai; Xu, Ke; Xu, Xuan; Zhu, Jixiang; Jin, Yinan; Liu, Qi; Xu, Rui; Gu, Xiaoping; Liu, Yue; Huang, Yulin; Ma, Zhengliang (Frontiers in Behavioral Neuroscience, 2022)
This study aims to explore the regulatory effect of S-ketamine on the mechanical allodynia, anxiety-like behaviors and microglia activation in adult male rats exposed to an animal model of post-traumatic stress disorder (PTSD). The rat PTSD model was established by the exposure to single prolonged stress (SPS), and one day later, rats were intraperitoneally injected with 5 mg/kg S-ketamine or normal saline, respectively. Paw withdrawal mechanical threshold was measured 2 days before, and 1, 3, 5, 7, 10, 14, 21 and 28 days after injection to assess mechanical allodynia in the SPS-exposed rats. For anxiety-like behaviors，the open field test and elevated plus maze test were performed at 7 and 14 days after S-ketamine treatment in the SPS-exposed rats, respectively. SPS-induced rats presented pronounced mechanical allodynia and anxiety-like behaviors, which were alleviated by S-ketamine treatment. After behavioral tests, rats were sacrificed for collecting the anterior cingulate cortex (ACC), prefrontal cortex (PFC), dorsal striatum, and periaqueductal grey (PAG). Protein levels of TNF-α, IL-1β, p-NF-κB and NF-κB in brain regions were examined by Western blot. In addition, microglia activation in each brain region was determined by immunofluorescence staining of the microglia-specific biomarker Iba-1. Interestingly, pro-inflammatory cytokines were significantly upregulated in the dorsal striatum and PAG, rather than ACC and PFC. Activated microglia was observed in the dorsal striatum and PAG as well, and upregulated p-NF-κB was detected in the dorsal striatum. Inflammatory response, phosphorylation of NF-κB and microglia activation in certain brain regions were significantly alleviated by S-ketamine treatment. Collectively, S-ketamine is a promising drug in alleviating mechanical allodynia, anxiety-like behaviors, and pro-inflammatory responses in discrete brain regions in a model of PTSD.